2011
DOI: 10.2147/vhrm.s14277
|View full text |Cite
|
Sign up to set email alerts
|

Early follow-up results of arteriovenous fistulae created for hemodialysis

Abstract: Background:The aim of this study was to evaluate the site, early results, and postoperative complications of arteriovenous f istula (AVF) creation procedures for hemodialysis in our clinic.Methods:The hospital records of 384 patients who underwent 411 AVF creation procedures for hemodialysis by the same team at our clinic between February 2008 and January 2010 were included for retrospective analysis. All procedures were performed under local anesthesia with lidocaine. Vasospasm was treated by mechanical dilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
2
16
0
1
Order By: Relevance
“…Miller et al [29] found Ithat the AVF maturation is more successful in men than in women. Similar results were obtained by Gibbons [30] and Iyem [31]. In our study, males were twice as likely to undergo fistula maturation, compared to that of females; the most rational explanation for this difference is the smaller size of vessels in women.…”
Section: Discussionsupporting
confidence: 91%
“…Miller et al [29] found Ithat the AVF maturation is more successful in men than in women. Similar results were obtained by Gibbons [30] and Iyem [31]. In our study, males were twice as likely to undergo fistula maturation, compared to that of females; the most rational explanation for this difference is the smaller size of vessels in women.…”
Section: Discussionsupporting
confidence: 91%
“…Iyem et al, reported the same highest complication rate of thromboses in a broad study population. [7] When we consider early complication rates we saw that high thrombosis rates especially in radiocephalic location were associated with anatomical limitations of surgery in this area where also most of bleeding and hematoma formations occurred. Radiocephalic location was announced in the literature as most common location for thrombosis in early period [8] as well.…”
Section: Discussionmentioning
confidence: 99%
“…16 Three patients had arm edema out of which one patient had non functioning fistula since first post operative day and was referred to vascular unit of other centre and edema subsided on its own in other 2 patients. One patient developed haematoma on first post operative day which was evacuated in operation theatre but fistula was functional and was patent at 6months follow up.…”
Section: 1116mentioning
confidence: 98%
“…The common complication of AVF surgery is thrombosis. 16 We have not used ultrasound Doppler for our patients due to lack of logistics so we were not able to detect the possible thrombosis causing failure in our unsuccessful cases (n=6).…”
Section: 1116mentioning
confidence: 98%